Islamic Religious Education Teachers' Strategies in Increasing Learning Motivation of Students from Economically Disadvantaged Families - Afifatus Tsurayya; Yudril Basith (Konsultan Jurnal Ilmiah Indonesia, 2025)
This study aims to examine various Islamic Religious Education (PAI) strategies that contribute to increasing the learning motivation of students from low-income families. Using a literature review approach, this article synthesizes previous research findings, Islamic education theory, and relevant pedagogical practices. Six key strategies were identified as effective in this context: instilling Islamic values as intrinsic motivation, exemplary Islamic Religious Education (PAI) teachers' lifestyle and teaching attitudes, a personal approach and humanistic relationships with students, reinforcement through non-classroom religious activities, providing non-material roles and appreciation, and integrating role models into learning. These strategies have been proven to foster a passion for learning, psychological resilience, and spiritual meaning in students, despite economic constraints. This article emphasizes that an empathetic, spiritual, and contextual approach to religious education can be an alternative solution to address the challenge of disparities in learning motivation among low-income students.